Injection bronchoplasty with carboxymethlycellulose with cystoscopy needle for neonatal persistent bronchopleural fistulae. (December 2019) - Beckmann, Nicholas; Luttrell, Jordan; Petty, Brad; Rhodes, Cecil; Thompson, Jerome
Abstract: Objective: We describe the novel use of injectable carboxymethylcellulose to close a persistent bronchopleural fistula (BPF) in a neonate who underwent an ex utero intrapartum treatment (EXIT) after aborted fetoscopy. Methods: In this case, a patient with laryngeal atresia underwent fetoscopy that was halted after concern for instruments within the mediastinum, and thus ultimately required an EXIT to establish an airway. Bilateral pneumothoraces and eventually multiple BPF were identified that continued to persist despite multiple attempts at removal of chest tubes over a four-week period. We look at the role of endoscopy and a substance often used in the larynx to help close a persistent BPF. Results: At initial bronchoscopy, no BPF was identified, but at subsequent evaluation due to persistent pneumothorax, we used increased positive end expiratory pressure to help reveal the fistula. Given the bronchial location of the fistula, traditional laryngeal instruments could not be used, requiring the use of urologic cystoscopy needles to assist in accessing these challenging locations. At postoperative day 2 from the injection, the chest tube was removed and did not require replacement. Conclusion: There are many methods to help treat BPF. The endoscopic injection of carboxymethylcellulose adds a technique to the pediatric otolaryngologist's armamentarium.